المؤرخ عبد الله بن بلقين (467 -483 هـ/ 1074-1090م) رائد كتابة "المذكرات الشخصية" في الأندلس - سلام، صلاح خليل إبراهيم (جامعة عين شمس - كلية الآداب, 2015)
يتضمن البحث دراسة للمؤرخ عبدالله بن بلقين (467-483ه/1074-1090م) رائد كتابة "المذكرات الشخصية" في الأندلس، وقد اشتمل البحث على معطيات عصر عبدالله بن بلقين، بحثت فيه مسألة الأندلس بعد انتهاء الدولة العامرية وبداية عهد الخذلان والتمزق السياسي والكساد الاقتصادي والتناحر العرقي مع تعاظم حركة الاسترداد على الرغم من الازدهار العلمي والثقافي، كما تناولت بالدراسة تأسيس دولة بني زيري في غرناطة مع التركيز على أحوالها في عهد عبدالله بن بلقين. وتتضمن البحث معالم الفكر التاريخي الأندلسي في عصر ابن بلقين ومقومات عقلية ابن بلقين التاريخية ونبذة عن أصله ومذهبه ووضعه الطبقي. كذلك تضمن البحث دراسة للقيمة التاريخية لكتاب التبيان من حيث تقديمه قراءة تفصيلية عن مملكة غرناطة وتأريخا لعصر ملوك الطوائف وتقييم هذه المذكرات بوصفها مصدرا مهما لدراسة التاريخ الأندلسي باعتباره عبدالله بن بلقين ليس مؤرخا فقط، وإنما شاهد عيان فاعل ومؤثر في وقائع عصره.
Research includes the study of the historian Abdullah bin Belkan, the leader of "personal notes" in Andalusia . It included the features of eraof Abdullah bin Belkan researched the tragedy of Andalusia after the falling of the state of Ameria and the beginning of the period of shames and distroy of political and economic states and fighting of nationalities with the great of the Christian policy of retaking their properities in spite of the bright of science and culture. The study dealt with the establishment of state of Beni Zere in Granada with a focus on their conditions in the reign of Abdullah bin Belkan. The research includes the historical landmarks in the era ofAbdullah bin Belkanand hiselements of mentality and historical overview of his origin and religion. As well as research has included the assessment and evaluation of these notes as an important source of studying the Anadalusian history especially in the period of the Tawifs Kings as he considered not only historian, but also an active eyewitness in his period .
Keywords: ابن بلقين، عبدالله -- الفكر التاريخي -- الأندلس -- الإنتاج الفكري -- كتاب المذكرات الشخصية فى الأندلس